An Overview about the chemical composition and Biological Activity of Medicinal species found in the Brazilian Amazon - Fernanda Brum Pires, Carolina Bolssoni Dolwitsch, Valéria Dal Prá, Débora Luana Monego, Viviane Maria Schneider, Roberta Fabrício Loose, Marcella Emília Petra Schmidt, Lucas P. Bressan, Marcio Antônio Mazutti, Marcelo Barcellos da Rosa, (Journal of Applied Pharmaceutical Science, 2016)
This paper presents an overview on the chemical composition and biological activity of plants found in the Brazilian Amazon – Bauhinia variegata, Cecropia obtusa, Cecropia palmata, Connarus perrottetti var. angustifolius, Chrysobalanus icaco and Mansoa alliacea. The lack of information regarding these species, along with their importance given their pharmacological and nutritional use in Latin American folk medicine, justifies the demand for this study. However, various interesting and important actions, as antioxidant, antibacterial, cytotoxic, hypoglycemic, antifungal, antiangiogenic, antitumor, anti-inflammatory, antiulcer, and chemopreventive have been modestly reported so far. In other words, these species can play a very important role in terms of biological and chemical activity, but their pharmacology is still poorly investigated. Accordingly, the discovery of molecules that could play a role against the major diseases of modern society could be achieved by paying more attention to plants used daily in some regions of our country.
Keywords: Biological activity,chemical composition,Brazilian Amazon,folk medicine.